Evaluasi dan Perbaikan Rancangan Antarmuka Pengguna Web Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kota Kediri menggunakan Metode Goal-Directed Design (GDD) - Nadhif Mahendra Putra; Intan Sartika Eris Maghfiroh; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The Office of Culture, Tourism, Youth and Sports (Disbudparpora) of the City of Kediri is a government agency that deals with cultural issues, manages tourism and youth sports activities in the City of Kediri. The staff who are responsible for managing the information media do not have new innovations regarding website design so it looks very monotonous. Therefore, it is necessary to recommend web design recommendations for the City of Kediri Disbudparpora so that the purpose of the recommendations is better for users. This user interface improvement will use the Goal-Directed Design (GDD) method which consists of six steps, the first of which is research on user desires. The second step is modeling which creates a persona. The third step is requirements that create scenario contexts and user requirements. The fourth step is the framework, namely making a wireframe. The fifth step is refinement which creates high-quality prototypes. Then the last step is support to do user testing and evaluation with the System Usability Scale (SUS) questionnaire. The User Testing process has obtained good results while the final evaluation has received an average score of 80.75 and is in the acceptable category in the acceptability ranges. Category B on the grade scale. The excellent category on the adjective rating and earned an A on the percentile rank. Therefore, the Disbudparpora improvement recommendation website is declared acceptable by users.